2009
DOI: 10.1007/s10461-009-9582-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Following Diagnosis with Acute/Early HIV Infection—A Move to Serosorting with Other HIV-Infected Individuals. The NIMH Multisite Acute HIV Infection Study: III

Abstract: Risk reductions behaviors are especially important during acute/early HIV infection, a period of high transmission risk. We examined how sexual behaviors changed following diagnosis of acute/early HIV infection. Twenty-eight individuals completed structured surveys and in-depth interviews shortly after learning of their infection and 2 months later. Quantitative analyses revealed significant changes after diagnosis, including reductions in total partners and decreases in the proportion of unprotected sex acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 27 publications
4
82
0
Order By: Relevance
“…This is largely due to individuals serving as possible links for viral transmission between their concurrent partners, particularly if safer sex is not always practiced. It has also been suggested that sexual concurrency can involve frequent switching between partners, which may allow viruses to spread quickly before individuals become aware of having been infected [5][6][7]. HIV, for example, is highly infectious when it is newly acquired [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to individuals serving as possible links for viral transmission between their concurrent partners, particularly if safer sex is not always practiced. It has also been suggested that sexual concurrency can involve frequent switching between partners, which may allow viruses to spread quickly before individuals become aware of having been infected [5][6][7]. HIV, for example, is highly infectious when it is newly acquired [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have documented that persons entering correctional facilities report high rates of HIV sex risk behaviors (e.g., mean number of partners 36.1; unprotected sex at last sex 70 %; 66 % with at-risk partner) before incarceration [13,32,33]. Prior research has documented that learning of one's HIV infection is associated with reductions in HIV risk behavior [34][35][36]. The majority of our study participants had become aware of their HIV infection before this incarceration and may have already reduced their sex risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…During AHI, the HIV-transmission risk is sharply elevated, and up to 40% of new HIV infections are attributed to transmission during this brief period of time [2]. Previous research has demonstrated that some individuals diagnosed with AHI continue to engage in sexual activity, including unprotected sex, suggesting that interventions beyond post-test counseling are needed to reduce forward transmission [3, 4]. Currently, no guidelines are available on the prevention of forward transmission of HIV during AHI and no behavioral interventions for individuals with AHI have been evaluated and published, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%